The association between the MAOA 2R genotype and delinquency over time among men: the interactive role of parental closeness and parental incarceration - Roettger, Michael E. (Criminal justice and behavior, 2016)
Using a panel of 6,001 males from the National Longitudinal Study of Adolescent and Adult Health, we examine potential moderation by paternal incarceration and parent?child closeness altering the relationship between the rare 2R MAOA genotype and delinquency. By jointly examining moderation patterns for both the mother and father with the transmission of the MAOA genotype from mother to son, we are able to make inferences about the specific genetic model that best explains these outcomes. In line with prior research, we find a direct relationship between the MAOA 2R genotype and delinquency, independent of parental incarceration and closeness. Examining moderation patterns, we find that delinquency risk for the 2R allele is buffered for males close to their biological or social father but not their biological mother. We conclude that the 2R-delinquency association is not due to passive gene?environment correlation but is best characterized as a social control Gene ? Environment interaction.